The Chemical Basis of Fungal Bioluminescence1. (11th June 2015) - Purtov, Konstantin V.; Petushkov, Valentin N.; Baranov, Mikhail S.; Mineev, Konstantin S.; Rodionova, Natalja S.; Kaskova, Zinaida M.; Tsarkova, Aleksandra S.; Petunin, Alexei I.; Bondar, Vladimir S.; Rodicheva, Emma K.; Medvedeva, Svetlana E.; Oba, Yuichi; et al.
Abstract Many species of fungi naturally produce light, a phenomenon known as bioluminescence, however, the fungal substrates used in the chemical reactions that produce light have not been reported. We identified the fungal compound luciferin 3‐hydroxyhispidin, which is biosynthesized by oxidation of the precursor hispidin, a known fungal and plant secondary metabolite. The fungal luciferin does not share structural similarity with the other eight known luciferins. Furthermore, it was shown that 3‐hydroxyhispidin leads to bioluminescence in extracts from four diverse genera of luminous fungi, thus suggesting a common biochemical mechanism for fungal bioluminescence.